Cevap :
☆Mєrhαbα☆
- [tex]3x - (2x - 3(x - 5) + 3x) = 9x - 20 \\ 3x - (2x - 3x + 15 + 3x) = 9x - 20 \\ 3x - (2x + 15) = 9x - 20 \\ 3x - 2x - 15 = 9x - 20 \\ x - 15 = 9x - 20 \\ 8x = 5 \\ x = \frac{5}{8} [/tex]
✨Anlamadığın bir yer olursa sorabilirsin✨
<3
#Pluwia
![Görseli göster Pluwia](https://tr-static.eodev.com/files/db1/0b9ba436c224c1e8e244d12dfac73c1f.jpg)
Cevap
5/8
3x-(2x+15)=9x-20
x-15= 9x-20
x-15-9x=-20
-8x=-20+15
-8x=-5
x=3/8
5/8
3x-(2x+15)=9x-20
x-15= 9x-20
x-15-9x=-20
-8x=-20+15
-8x=-5
x=3/8